Development and Validation of a Simplified Probability Assessment Score Integrated With Age‐Adjusted d‐Dimer for Diagnosis of Acute Aortic Syndromes - Morello, Fulvio (J Am Heart Assoc, 2021)
BACKGROUND: When acute aortic syndromes (AASs) are suspected, pretest clinical probability assessment and d‐dimer (DD) testing are diagnostic options allowing standardized care. Guidelines suggest use of a 12‐item/3‐category score (aortic dissection detection) and a DD cutoff of 500 ng/mL. However, a simplified assessment tool and a more specific DD cutoff could be advantageous. METHODS AND RESULTS: In a prospective derivation cohort (n=1848), 6 items identified by logistic regression (thoracic aortic aneurysm, severe pain, sudden pain, pulse deficit, neurologic deficit, hypotension), composed a simplified score (AORTAs) assigning 2 points to hypotension and 1 to the other items. AORTAs≤1 and ≥2 defined low and high clinical probability, respectively. Age‐adjusted DD was calculated as years/age × 10 ng/mL (minimum 500). The AORTAs score and AORTAs≤1/age‐adjusted DD rule were validated in 2 patient cohorts: a high‐prevalence retrospective cohort (n=1035; 22% AASs) and a low‐prevalence prospective cohort (n=447; 11% AASs) subjected to 30‐day follow‐up. The AUC of the AORTAs score was 0.729 versus 0.697 of the aortic dissection detection score (P=0.005). AORTAs score assessment reclassified 16.6% to 25.1% of patients, with significant net reclassification improvement of 10.3% to 32.7% for AASs and −8.6 to −17% for alternative diagnoses. In both cohorts, AORTAs≥2 had superior sensitivity and slightly lower specificity than aortic dissection detection ≥2. In the prospective validation cohort, AORTAs≤1/age‐adjusted DD had a sensitivity of 100%, a specificity of 48.6%, and an efficiency of 43.3%. CONCLUSIONS: AORTAs is a simplified score with increased sensitivity, improved AAS classification, and minor trade‐off in specificity, amenable to integration with age‐adjusted DD for diagnostic rule‐out.